Predictors of treatment response to psychological interventions in people at clinical high risk of first‐episode psychosis. Issue 1 (4th July 2017) - Wessels, Helen; Wagner, Michael; Kuhr, Kathrin; Berning, Julia; Pützfeld, Verena; Janssen, Birgit; Bottlender, Ronald; Maurer, Kurt; Möller, Hans‐Jürgen; Gaebel, Wolfgang; Häfner, Heinz; Maier, Wolfgang; et al.
Abstract : Aim: Psychological interventions, such as cognitive behavioural therapy (CBT) and supportive counselling (SC), are used to treat people with schizophrenia and people at clinical high risk (CHR) of psychosis. However, little information is available on predictors of treatment response. This study aims to identify such predictors of psychological interventions in CHR. Methods: A total of 128 help‐seeking CHR outpatients were randomized into two groups—integrated psychological intervention (IPI), including CBT, and SC—for 12 months. Multiple regression analysis was used to identify demographic, symptomatic and functional variables that predict improvement in positive (PANSS Positive), negative (PANSS Negative) and basic symptoms (Basic symptom total score) and improvement in functioning (GAF) at 1‐year follow up. Results: In the merged group (IPI + SC), people who lived independently, were younger and presented with higher baseline functioning showed more improvement in symptomatic outcomes at follow up. Negative symptoms at baseline predicted less improvement in positive and basic symptoms. Being married or cohabiting and living in the primary family were found to correlate with good functioning at 1‐year follow up. Conclusions: Younger CHR individuals and those who are functioning well may particularly benefit from early intervention. Treatment might need to be modified for low‐functioning CHR and those who already display higher scores of negative symptoms. Registration number: NCT00204087